Are regional crime rates in India natural? - Ohlan, Ramphul (Crime, Law & Social Change, 2020)
Crime has been around for as long as the human society. The present study examines whether there is a natural rate of crime in India at both national and state-level using annual data for aggregate and specific crime types. The presence of unit root in crime rate series has been investigated by accommodating endogenously determined structural break point. The empirical analysis indicates that most of the regional crime rates series are stationary which implies the existence of natural rate of crime in India. Based on our findings it is suggested that India should focus on improving the socioeconomic status of the general masses instead of devoting more resources to short-term measures of reducing crime rates. In addition, the state-level social profiles should be taken into consideration for articulating crime-fighting policies.